HIV testing at a community health center before and after implementing universal screening. Issue 8 (August 2016) - Kayingo, Gerald; Bruce, Robert Douglas
Abstract : ABSTRACT: This study analyzed the quality of HIV screening at one of the largest community health centers in Connecticut. The data indicated that implementing universal HIV screening increased the proportion of underrepresented minorities and women tested, reducing the HIV testing disparities that previously existed at this center.